Static Pull Testing of a New Type of Large Deformation Cable with Constant Resistance. (16th March 2017) - Tao, Zhigang; Pang, Shihui; Zhou, Yijun; Zhang, Haijiang; Peng, Yanyan
Abstract : A new type of energy-absorbing cable, Constant-Resistance Large Deformation cable (CRLD cable) with three different specifications, has been recently developed and tested. An effective cable should occupy the ability of absorbing deformation energy from these geodisaster loads and additionally must be able to yield with the sliding mass movements and plastic deformation over large distances at high displacement rates. The new cable mainly consists of constant-resistance casing tube and frictional cone unit that transfers the load from the slope. When experiencing a static or dynamic load and especially the load exceeding the constant resistance force (CR-F, a static friction force derived from the movement of frictional cone unit in casing tube) of CRLD cable, the frictional cone unit will move in the casing tube along the axis and absorb deformation energy, accordingly. In order to assess the performance of three different specified cables in situ, a series of field static pull tests have been performed. The results showed that the first type of CRLD cable can yield 2000 mm displacement while acting 850 kN static pull load, which is superior to that of other two types, analyzing based on the length of the displacement and the level of static pull load.